Problematika Penentuan Hari Tarwiyah dan Arafah dalam Perspektif Ilmu Falak - Marataon Ritonga; Arwin Juli Rakhmadi; Hariyadi Putraga; Muhammad Hidayat (Astroislamica: Journal of Islamic Astronomy, 2023)
For a long time, Muslims were facing problems related to the determination of the Tarwiyah and the Arafat fasting day. In this case, whether Muslims should follow the Saudi Arabian calendar or the local one. In this study, Muslims differ in opinion, some argue that they should follow the Saudi Arabia calendar and others say that enough to follow the national calendar. The absence of unified calendar resulted in many problems faced by Muslims in assigning their holidays such as Ramadan, Shawwal, and Dhulhijah. To achieve Muslim unification in conducting various religious rituals, Muslims must have a unification dating system in order to realize togetherness in determining the worshipping time. This research is literature research. Thus the data that used in the form of books, journals, and other references. The results concluded that the determination of Tarwiyah and f Arafat Day until now still provides dispute among Muslims, there are those who argue specifically in determining the Dhulhijah beginning must be oriented to the Saudi Arabia kingdom’s determination. While others argue that assigning the worshipping time does not have to follow Saudi Arabia, just adhering to the nation’s determination